Effects of collagen-induced rheumatoid arthritis on amyloidosis and microvascular pathology in APP/PS1 mice - Park, Sun Mi (BioMed Central, 2011)
BACKGROUND: Evidence suggests that rheumatoid arthritis (RA) may enhance or reduce the progression of Alzheimer's disease (AD). The present study was performed to directly explore the effects of collagen-induced rheumatoid arthritis (CIA) on amyloid plaque formation, microglial activation, and microvascular pathology in the cortex and hippocampus of the double transgenic APP/PS1 mouse model for AD. Wild-type or APP/PS1 mice that received type II collagen (CII) in complete Freund's adjuvant (CFA) at 2 months of age revealed characteristics of RA, such as joint swelling, synovitis, and cartilage and bone degradation 4 months later. Joint pathology was accompanied by sustained induction of IL-1β and TNF-α in plasma over 4 weeks after administration of CII in CFA. RESULTS: CIA reduced levels of soluble and insoluble amyloid beta (Aβ) peptides and amyloid plaque formation in the cortex and hippocampus of APP/PS1 mice, which correlated with increased blood brain barrier disruption, Iba-1-positive microglia, and CD45-positive microglia/macrophages. In contrast, CIA reduced vessel density and length with features of microvascular pathology, including vascular segments, thinner vessels, and atrophic string vessels. CONCLUSIONS: The present findings suggest that RA may exert beneficial effects against Aβ burden and harmful effects on microvascular pathology in AD.